Effects of extraction methods on the structural characteristics and functional properties of dietary fiber extracted from papaya peel and seed - Feng, Xiaoyu; Ameer, Kashif; Jiang, Guihun; Ramachandraiah, Karna (Frontiers in Sustainable Food Systems, 2024)
This study aimed to characterize dietary fibers (DF) produced from papaya peel (PP) and seed (PS) using three different extraction methods (acidic: AC, enzymatic: EN and alkaline: AL). The scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR), thermal and rheological properties, X-ray diffraction (XRD), monosaccharide composition were adopted for characterizing DF samples. All the DF samples showed representative infrared spectral features and crystalline structure, whereas DF derived from PP and PS extracted by AC had looser and more complicated structures. DF derived from PP and PS extracted by EN displayed greater thermal stability among DFs. DF extracted by PP-AC and PS-EN showed a high degree of linearity in rheograms as compared to other DF samples. In addition, the extraction method also influenced the monosaccharide composition in PP and PS DFs samples. Furthermore, AC-extracted DFs, specifically PP-AC and PS-AC exhibited higher functional (water-holding capacity (WHC), oil-holding capacity (OHC), water swelling capacity (WSC), cholesterol-absorption capacity (CAC), bile acid absorption capacity (BAC), nitrite ion absorption capacity (NIAC), glucose absorption capacity (GAC)) and antioxidant properties (DPPH, ABTS and FRAP). Our results suggest that the PP and PS derived DF samples could potentially be used as functional food ingredient.